1996
DOI: 10.1007/bf02185758
|View full text |Cite
|
Sign up to set email alerts
|

Deletions of the long arm of chromosome 10 in progression of follicular thyroid tumors

Abstract: Previous studies of follicular thyroid tumors have shown loss of heterozygosity (LOH) on the short arm of chromosome 3 in carcinomas, and on chromosome 10 in atypical adenomas and carcinomas, but not in common adenomas. We studied LOH on these chromosomal arms in 15 follicular thyroid carcinomas, 19 atypical follicular adenomas and 6 anaplastic (undifferentiated) carcinomas. Deletion mapping of chromosome 10 using 15 polymorphic markers showed that 15 (37.5%) of the tumors displayed LOH somewhere along the lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
35
1

Year Published

1997
1997
2000
2000

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 24 publications
4
35
1
Order By: Relevance
“…Moreover, loss of heterozygosity on chromosome 10q22 has been observed in two follicular carcinomas adjacent to an area of anaplastic carcinomas (29,30). These data would support the involvement of other suppressor genes in the progression process leading to the anaplastic phenotype.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, loss of heterozygosity on chromosome 10q22 has been observed in two follicular carcinomas adjacent to an area of anaplastic carcinomas (29,30). These data would support the involvement of other suppressor genes in the progression process leading to the anaplastic phenotype.…”
Section: Discussionmentioning
confidence: 59%
“…Recent studies have shown that the distal region of chromosome 10q is commonly deleted in glioma, lung cancer, melanoma, prostate cancer, bladder cancer, and thyroid tumor. 12,15,16,20,37) These results indicate that there are putative tumor suppressor gene(s) on the distal region of 10q, which are involved in various types of carcinomas.…”
Section: Discussionmentioning
confidence: 90%
“…Clearly, the existence of such candidate genes, which are lost in the samples studied here, remains to be determined. Analysis of LOH in a variety of tumours has suggested that multiple discrete regions of chromosome 10 loss may occur in a single tumour or tumour type (Parmiter et al, 1988;Karlbom et al, 1993;Herbst et al, 1994;Peiffer et al, 1995;Albarosa et al, 1996;Ittmann, 1996;Trybus et al, 1996;Zedenius et al, 1996;Marsh et al 1998b). The precise physical localization of such deleted regions with respect to one another and the number of tumoursuppressor genes they represent has been difficult to determine, in part because of the variety of markers used in the different studies.…”
Section: Discussionmentioning
confidence: 99%